2017
DOI: 10.1039/c7ra12062a
|View full text |Cite
|
Sign up to set email alerts
|

Improving osteogenesis of PLGA/HA porous scaffolds based on dual delivery of BMP-2 and IGF-1viaa polydopamine coating

Abstract: To engineer bone tissue, an ideal biodegradable implant should be biocompatible, biodegradable, osteoinductive and osteoconductive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 43 publications
(52 reference statements)
3
68
0
Order By: Relevance
“…Although it might avoid the excessive burst release of BMP-2 in this biodegradable delivery system, gelatin microspheres in our study could degrade earlier than PLGA microspheres, and porosity created by degradation of gelatin microspheres in the PLGA matrix would be useful for bone healing [38]. By surface binding technology such as polydopamine-assisted immobilization of BMP-2, some researchers found it can effectively enhance BMP-2 binding on the surface of the PLGA scaffold, and the BMP-2 can be slowly released over three weeks in vitro [14]. However, poor biocompatibility in vitro and insufficient release time in vivo were observed, which was not sufficient to achieve complete defect filling [46].…”
Section: Cell Proliferation and Differentiation In Plga Plga/gms Andmentioning
confidence: 76%
See 1 more Smart Citation
“…Although it might avoid the excessive burst release of BMP-2 in this biodegradable delivery system, gelatin microspheres in our study could degrade earlier than PLGA microspheres, and porosity created by degradation of gelatin microspheres in the PLGA matrix would be useful for bone healing [38]. By surface binding technology such as polydopamine-assisted immobilization of BMP-2, some researchers found it can effectively enhance BMP-2 binding on the surface of the PLGA scaffold, and the BMP-2 can be slowly released over three weeks in vitro [14]. However, poor biocompatibility in vitro and insufficient release time in vivo were observed, which was not sufficient to achieve complete defect filling [46].…”
Section: Cell Proliferation and Differentiation In Plga Plga/gms Andmentioning
confidence: 76%
“…Consequently, the enrichment of CPC/PLGA with osteoinductive factors is necessary to improve their biological performance. PLGA/HA scaffolds combined with osteoinductive growth factor via polydopamine were fabricated by some studies, but based on its high porosity, the low mechanical strength, which can influence osteogenesis, has yet to be solved [14]. A wide number of PLGA composite in combination with gelatin (PLGA/gelatin) are being studied as a new type of alternatives for bone tissue regeneration [15].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Recent studies have shown that the combined delivery of BMP-2 and IGF-1 enhances tissue regeneration compared to single growth factor delivery. [11] Lu et al investigated the use of biodegradable hydrogel composite scaffolds to deliver BMP-2 and IGF-1 for the repair of osteochondral tissue in a rabbit model. [12] Their results suggested that the fast release of BMP-2 followed by a slow and sustained release of IGF-1 synergistically enhance the degree of subchondral bone formation.…”
Section: A Poly(lactic-co-glycolic Acid)-poly(ethylene Glycol)-carboxmentioning
confidence: 99%
“…For PLGA materials in particular, many researchers have fabricated PLGA scaffolds for bone defect repair; they show good biocompatibility, low immunogenicity, and toxicity and are widely used in pharmaceutical and tissue engineering as an FDA certificated medical materials. However, PLGA scaffolds have hydrophobic surfaces and unsatisfactory mechanical properties, which have restricted its regenerative stimulation of large bone defects [8]. Therefore, in order to improve the bioactivity of PLGA, various chemical or physical methods have been employed, such as plasma treatment, photoreactive gelatin, poly(dopamine) coating, and nanoparticle doping [9][10][11].…”
Section: Introductionmentioning
confidence: 99%